The Marriage Age U-Shape - Pavel Jelnov (Institute of Labor Economics (IZA), 2019)
In this paper, I address the U-shaped dynamics (a decrease followed by an increase) in the age at first marriage during the twentieth century. First, I show that the U-shaped dynamics have been steeper in Western that in other countries. Second, I find that these dynamics in Western Europe are strongly related to the post-WWII economic development. By contrast, in the nineteenth and the first half of the twentieth centuries age of marriage was much less correlated across Western countries. I propose a simple model where age of marriage is a function of search frictions and a structural change of the economy. Both factors put together generate U-shaped dynamics as a result of an industrial boom that mimics the post-WWII economic development, especially in Western countries.
Keywords: J12; N32; N34; 330; age of marriage; economic development; twentieth century demography